2020
DOI: 10.1021/acs.jproteome.0c00508
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium(IV)-IMAC Revisited: Improved Performance and Phosphoproteome Coverage by Magnetic Microparticles for Phosphopeptide Affinity Enrichment

Abstract: Phosphopeptide enrichment is an essential step in large-scale, quantitative phosphoproteomics by mass spectrometry. Several phosphopeptide affinity enrichment techniques exist, such as Immobilized Metal ion Affinity Chromatography (IMAC) and Metal Oxide Affinity Chromatography (MOAC). We compared Zirconium(IV) IMAC (Zr-IMAC) magnetic microparticles to more commonly used Titanium(IV) IMAC (Ti-IMAC) and TiO2 magnetic microparticles for phosphopeptide enrichment from simple and complex protein samples prior to ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 77 publications
1
29
0
Order By: Relevance
“…A recent study demonstrated the improved performance of Zr-IMAC, Ti-IMAC, and TiO2-MOAC following optimization of the binding solvent used during the enrichment protocol. Following optimization, a comparison of the number of phosphopeptides identified between these techniques, as well as the most commonly used Fe-IMAC, revealed that microparticle-based Zr-IMAC enrichment was superior resulting in a higher phosphoproteome coverage [75]. This study also reinforced the widely documented view that combining enrichment techniques results in more robust PTM-focused MS-based analyses.…”
Section: Phosphorylationmentioning
confidence: 52%
“…A recent study demonstrated the improved performance of Zr-IMAC, Ti-IMAC, and TiO2-MOAC following optimization of the binding solvent used during the enrichment protocol. Following optimization, a comparison of the number of phosphopeptides identified between these techniques, as well as the most commonly used Fe-IMAC, revealed that microparticle-based Zr-IMAC enrichment was superior resulting in a higher phosphoproteome coverage [75]. This study also reinforced the widely documented view that combining enrichment techniques results in more robust PTM-focused MS-based analyses.…”
Section: Phosphorylationmentioning
confidence: 52%
“…These materials are commercially available and immobilized on diverse supporting matrices for different ways of handling, such as in an agarose resin spin‐down column from Thermo Scientific ™ Pierce ™ , the TiO 2 resin column from Titansphere ® , or in the form of magnetic beads from Cytiva. These different phosphopeptide enrichment approaches result in different phosphopeptides identified (Arribas Diez et al., 2021; Gates et al., 2010; Liang et al., 2007), suggesting that different matrices enrich slightly different types of phosphopeptides. New supporting matrices are continuously being developed (Kupcik et al., 2019).…”
Section: Commentarymentioning
confidence: 99%
“…To date, several emerging methods based on different principles have been developed for PTMs protein sample preparation and enrichment. For example, the enrichment strategies operated in phosphoproteomic studies are molecularly imprinted technology (MIP) [25, 26], ion exchange chromatography (IEC) [27–29], affinity chromatography [30–32], and chemical derivatization [33, 34]. Different from phosphorylation modifications with fixed structures, the diversity of polysaccharides and the interference of glycans on the peptide backbone make the identification of glycopeptides and the study of protein glycosylation encounter more obstacles.…”
Section: Introductionmentioning
confidence: 99%